Familial amyotrophic lateral sclerosis: a report of two cases - Zeng LI; Jun-Jian ZHANG (Yixue xinzhi zazhi)
Amyotrophic lateral sclerosis (ALS), the most common motor neuron disease in adults, is characterized by progressive loss of upper and lower motor neurons. Mutations in the superoxide dis-mutase gene (SOD1) account for about 20% of familial ALS cases. Here, we report Gly148Asp mutations in the exons of the SOD1 gene in two patients with familial ALS characterized by rapid progression of the disease, primarily affecting inferior motor neurons. Both patients developed severe systemic muscle atrophy and respiratory failure within one year of onset, having a short survival time.